2015
DOI: 10.1016/j.techfore.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Fostering breakthrough technologies — How do optimal funding decisions depend on evaluation accuracy?

Abstract: There is a growing interest in fostering breakthrough technologies that offer exceptionally high value to society. However, when starting technology projects, it is impossible to know which of them have the potential to lead to breakthroughs. Therefore, organizations have adopted funding policies in which on-going projects are subjected to interim evaluations based on which some projects may be abandoned to release resources for seizing new opportunities. In this paper, we study which funding policies are opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Muscio, et al (2013) showed that the government funding to universities complements funding from research contracts and consulting, contributing to increasing universities' collaboration with industry and activating knowledge transfer processes. Vilkkumaa et al (2015) investigated optimal funding decisions depending on evaluation accuracy. Focusing upon the policies maximizing the expected value of the project portfolio, they showed that the optimal policy for funding exceptionally excellent projects was to start a large number of projects and abandon a high proportion of them later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscio, et al (2013) showed that the government funding to universities complements funding from research contracts and consulting, contributing to increasing universities' collaboration with industry and activating knowledge transfer processes. Vilkkumaa et al (2015) investigated optimal funding decisions depending on evaluation accuracy. Focusing upon the policies maximizing the expected value of the project portfolio, they showed that the optimal policy for funding exceptionally excellent projects was to start a large number of projects and abandon a high proportion of them later.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing upon the policies maximizing the expected value of the project portfolio, they showed that the optimal policy for funding exceptionally excellent projects was to start a large number of projects and abandon a high proportion of them later. In general, Vilkkumaa et al (2015) emphasize that the optimal policy for maximizing the expected value of the project portfolio is to grant long-term funding to a smaller set of projects based on initial evaluation. McKinney and Hagedorn (2017) proposed a performance-based funding model for community colleges in Texas, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Can such a staging approach also be used by science funding agencies, allowing them to take more risk? Interim evaluation is especially useful when initial estimates are unreliable, but can be quickly updated and when investments can start at small scale and can be later scaled up (Vilkkumaa et al 2015). It is thus especially suitable for research that can make substantial steps forwards in a relatively short period of time and does not require large fixed-costs to be started (Ewens, Nanda, and Rhodes-Kropf 2018).…”
Section: Stagingmentioning
confidence: 99%
“…While their importance has been highlighted in the literature, and is likely to only increase (Colombo et al, 2011), there are still important issues which remain unresolved. Firstly, the qualitative and analytical models using market failure theory to justify STI policy are potentially limited when the innovation in question are related to transformational shifts and grand challenges (Nelson, 1994;Mazzucato, 2013a), and secondly, solid quantitative and empirical models to support the design of policies promoting technological breakthrough innovation are still scarce (Vilkkumaa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%